Nutrition for travel: From jet lag to catering - Halson, S. L.; Burke, L. M.; Pearce, J. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
Domestic and international travel is a common component of an elite athlete`s yearly plan. Track-and-field athletes may travel to weekly competition in different countries during the main season (e.g., Diamond League), whereas distance runners and race walkers may complete less frequently in race series spread over several continents. National, regional, and World Championship competitions are held in different cities on annual/biennial schedules, while the Olympic Games held every 4 years typically involve reconnaissance trips and staging camps to familiarize athletes with the characteristics of the host environment. Meanwhile, specialized training camps targeting heat, altitude, or a dedicated training focus may also require international travel.